1996
DOI: 10.1172/jci118872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on kinetics of nitric oxide release in rat aorta and pulmonary artery.

Abstract: Aging is an important determinant of vascular disease. Endothelium-derived nitric oxide (NO) is protective as a vasodilator and inhibitor of platelet function. This study was designed to directly measure effects of prolonged aging on endothelial NO release in isolated blood vessels and to delineate differences between the systemic and pulmonary circulation.Aortas and pulmonary arteries from 5-6-mo-old (young), 18-19-mo-old (middle-aged), and 32-33-mo-old (old) normotensive female rats were used. Blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(170 citation statements)
references
References 35 publications
8
160
2
Order By: Relevance
“…Angiogenesis is a complex process that includes activation, migration, and proliferation of endothelial cells. 19 Recent studies [21][22][23][24] have indicated that the integrity of endothelial cell function may be compromised as a function of advanced age. We confirmed that endothelial function was abnormal in old versus young rabbits by documenting impaired vasodilation in response to the endothelium-dependent vasodilator acetylcholine in vivo and reduced release of NO from isolated blood vessels studied ex Representative examples of collateral vessel formation in old rabbits (A), old VEGF-treated rabbits (B), young rabbits (C), and young VEGF-treated rabbits (D).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is a complex process that includes activation, migration, and proliferation of endothelial cells. 19 Recent studies [21][22][23][24] have indicated that the integrity of endothelial cell function may be compromised as a function of advanced age. We confirmed that endothelial function was abnormal in old versus young rabbits by documenting impaired vasodilation in response to the endothelium-dependent vasodilator acetylcholine in vivo and reduced release of NO from isolated blood vessels studied ex Representative examples of collateral vessel formation in old rabbits (A), old VEGF-treated rabbits (B), young rabbits (C), and young VEGF-treated rabbits (D).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction may be due to diminished bioavailability of nitric oxide (Taddei et al, 2001; Tschudi et al, 1996). Arterial stiffness results primarily from loss of elastic fibers and an increase in collagen (Fritze et al, 2012).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%
“…Direct in situ measurements of NO were carried out using a three-electrode system: a porphyrinic NO microsensor as the working electrode (anode), a platinum wire auxiliary electrode (cathode), and a standard calomel reference electrode (Azhar et al, 1995;Tschudi et al, 1996). Amperometric mode detection was used at a constant potential, equal to the peak potential for NO oxidation of the working electrode.…”
Section: Measurement Of Superoxide (Aging Lps)mentioning
confidence: 99%
“…This enzyme is largely membrane associated as a result of NH 2 -terminal myristoylation (Pollock et al, 1991), a reaction which regulates enzymatic biological activity (Sessa et al, 1993;Busconi and Mitchel, 1993). Endothelium-dependent relaxation 8-2 declines with increasing age (Tschudi et al, 1996). The underlying cellular and molecular mechanisms associated with age-related endothelial dysfunction have not been elucidated, but might involve: (a) changes in expression and/or activity of eNOS (Cernadas et al, 1998), (b) increased breakdown of NO due to an augmented production of • O 2 - (Gryglewski et al, 1986), or (c) a gradual loss of antioxidant capacity (Azhar et al, 1995), which normally provides cellular protection against reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%